Kusch y la verdad radicalmente situada. Una perspectiva decolonial de la historia - Gay, Eugenia (Historiografías, 2024)
AbstractThe article examines the conception of history presented throughout the different works of the philosopher Rodolfo Kusch. His criticism of the so-called mestizo historiography is articulated on a broader conception of culture as an ethical option configured from the historical-political response of every society to the fear that characterizes existence. This response, categorized as learned or popular thinking, as being or being-there, as logical or seminal thinking, configures specific ways of considering historical events and the truth of history. It also allows us to understand disputes over historical truth not only as a result of disciplinary or philosophical logic, but as a survival strategy at the level of situated experience.KeywordsRodolfo Kusch, philosophy of history, situated thinking